Finland : 2016 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Finland. (IMF Staff Country Reports; Country Report ;, 2016)
This 2016 Article IV Consultation highlights that the growth in Finland has turned tepidly positive again following a deep recession. GDP increased by 0.2 percent in 2015 driven by stronger private consumption and a rebound in investment. Although net export growth was weak, falling oil prices contributed to the nominal trade balance shifting into surplus, reducing the current account deficit. Better-than-expected fiscal performance brought the deficit back under the 3 percent Stability and Growth Pact limit in 2015. The recovery is likely to continue, but growth is set to remain slow at about 0.9 percent in 2016 and 1.1 percent in 2017. This outlook is subject to downside risks.